2D Public Service Announcement: Challenge Home-based Learning during Pandemic on University Students - Emma Izzany Azhar; Hanif Faiq Mohd Hashim (Journal of Computing Technologies and Creative Content, 2022)
Home-based learning (HBL) was aimed to help teachers in implementing home-based teaching and learning as an alternative to learning new norms. To ensure contact between teachers and students, home-based learning is implemented online using online communication apps such as Google Meet, Microsoft Teams, and numerous accessible services such as video conferencing. Over an amount of time, students use a screen device such as a computer, laptop, tablet, or smartphone. Technology is important, but there are many factors to consider when creating online learning environments that are truly engaging for students. This research is to study on the challenges of home-based learning during the pandemic that impact to university students. The focus of the research will cover several elements such as style infographic, visualization, illustration, and audio. Also, this research will evaluate the effectiveness among selected respondents regarding the 2D Public Service Announcement (PSA). The model chosen is the ADDIE model which is Analysis, Design, Development, Implementation and Evaluation as the technique to follow. Therefore, I hope that this research will provide a better informed and awareness by using this method among university students in Malaysia.